Impact of migration test method on the release of silver from nanosilver-polyethylene composite films into an acidic food simulant. (December 2017) - Wu, Li-Bing; Su, Qi-Zhi; Lin, Qin-Bao; Peng, Wei-Dong; Chen, Chao-Fang; Wang, Zhi-Wei; Hu, Chang-Ying
Highlights: Migration test method's effect on nanosilver release differ from that on common migrants' migration. Two-sided contact results in higher silver release than one-sided one. Increasing the number of cut edges increases silver release. Metal migration cell leads to lower silver release. Abstract: Impact of migration test method on the release of nanocomponent from nano-polymer composite films intend for food contact is seldom addressed. In this study, release of silver from nanosilver-polyethylene composite films into 3% acetic acid under different migration test methods were investigated, with the aim to understand the effect of exposure condition on silver release. The following test protocols were designed for the experiment: single-sided contact versus two-sided contact, more versus fewer cut edges, and glass migration cell versus metal one. The results show that samples under two-sided contact had higher silver release than that under one-sided contact. Besides, increasing the number of cut edges largely increased the release of silver, while using metal instead of glass migration cell significantly reduced the release. Furthermore, partially floated films have lower silver release than that of totally immersed films. As a conclusion, impact of migration test method on the release of nanocomponent is different from that on the migration of common migrants and therefore, exposure condition should be carefully taken into account in the design of migration test for nanosilver-polyethylene composite films to minimize any potential negative impact on obtaining comparable results.